لفظ الھدی کی معنوی جہات:علم الوجوہ والنظائر کی روشنی میں منتخب تفاسیر کا تحقیقی مطالعہ : The Semantic Aspects of the Word Al-Hadi: A Research Study of Selected Interpretations in the Light of Illum al-wjwah and Wanazair - Muhammad Ishfaq; Prof. Dr. Shahida Parveen (International Research Journal of Arabic and Islamic Studies, 2024)
The main subject of the Holy Qur'an is man, and the first purpose of the revelation of the Qur'an is the reformation of man. There is also Achieving the main purpose of the revelation of the Qur'an will be possible only when it is fully understood and familiar with its words and meanings. For the understanding of the Qur'an, where other sciences such as the knowledge of the revelation of the revelation, the knowledge of abrogation and cancellation, the knowledge of the poor Qur'an, etc. It is necessary to acquire an important knowledge of Al-Qur'an sciences, "Ilm al-Ujwah wal-Nazir".